The Europeanisation of development policy: acceptance, accommodation and resistance of the Czech Republic - Ondrej Horký (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
In the first step, a framework for Europeanisation, defined as adoption of EU rules by the member states, is adjusted to the field of development policy. As the acquis in this field of shared competence between the Commission and the member states consists almost entirely of soft law, social learning and, to a lesser extent, global incentives and lesson-drawing are identified as the dominant models of Europeanisation. Thereafter, the attitudes of member states to the EU development policy, characterised by the normative power of the Commission and the strong influence of foreign policy, are analysed, and the informal rules of policy-making that are not enshrined in EU legislation are complemented by this section. Finally, the Europeanisation framework is applied to the Czech Republic. The shallow Europeanisation of the Czech development cooperation is explained by the differences of values and norms shared at the EU and the national level, and the difference in the perception of the most efficient level in promoting the long-term national interests. An analysis of the Czech discourse, the institutionalisation and implementation of the norms on aid quality and quantity, the “3 Cs” agenda and the focus on Africa shows that resistance and accommodation are more frequent modes of dealing with EU rules than their acceptance. The paper concludes with a scrutiny of the EU's failure to promote its norms in development policy among the member states.
Keywords: 330